ENHANCING ACTIVE-PASSIVE SENTENCES SKILLS OF 1ST SEMESTER STUDENTS BY IMPLEMENTING REED-KELLOGG SYSTEM - Ade Kristianus Kaloeti (Merwinspy Publisher, 2025)
This study aims to investigate the impact of the Reed-Kellogg System of sentence diagramming on the enhancement of understanding active and passive sentences in English among first-semester students in the Bachelor's program of Management and the Diploma program in Accounting. The research employs a quantitative experimental design, where data is collected from an experimental group that receives instruction through the Reed-Kellogg sentence diagramming method and a control group that is taught using conventional methods. The sample consists of 16 students in the experimental group and 16 students in the control group. Statistical analysis, including Paired-Sample t-tests, Independent-Sample t-tests, and N-Gain Scores, is conducted using SPSS version 22. The research findings indicate that the significance values (2-tailed) obtained from both the Paired-Sample t-Test and the Independent Sample t-Test are 0.000. This value is less than the threshold of 0.05, leading to the acceptance of the hypothesis that the Reed-Kellogg sentence diagramming method has an effect on the mastery of active and passive sentences in English among first-semester Management and Accounting students. However, the N-Gain Score percentage of 34.15 suggests that the Reed-Kellogg sentence diagramming method may not be effective for teaching active and passive sentences in English to first-semester Management and Accounting students.